A Defense of the Whole-Brain Concept of Death - Bernat, James L. (The Hastings Center report, 1998)
The concept of whole-brain death is under attack again. Scholars are arguing that the concept of brain death per se—regardless of the focus on “higher,” “stem” or “whole”—is fundamentally flawed. These scholars have identified what they believe are serious discrepancies between the definition and criterion of brain death, and have pointed out that medical professionals and lay persons remain confused about its meaning. Yet whole-brain death remains the standard for determining death in much of the Western world and its defenders believe this concept best maps onto our everyday conception of death.